Lipoma arborescens of the elbow: a case with features of a high-grade tumor - Wagner Santana Cerqueira; Rayssa Araruna Bezerra de Melo; Felipe D'Almeida Costa; Juliane Comunello; Almir Galvão Vieira Bitencourt; Wu Tu Chung (Revista Brasileira de Ortopedia)
ABSTRACT Lipoma arborescens (LA) is an uncommon non-neoplastic disorder that may affect almost any joint, mainly the knee. LA is very rare in the elbow, and there are only a few cases reported in the literature. This study aimed to describe a case of LA in the elbow, presenting with features of a high-grade tumor. The authors report the case of a 51-years-old male who presented to this institution with pain and swelling on the left elbow. The patient had a seven-year history of investigation, with inconclusive diagnosis. Magnetic resonance imaging (MRI) showed an expansive mass with local aggressiveness. Due to these characteristics, it was not possible to discard soft tissue sarcoma at the differential diagnosis. After biopsy and a multidisciplinary team meeting, the authors opted for surgical resection. The final anatomopathological result confirmed the diagnosis of LA. Despite not being a true neoplasm, LA can cause many symptoms and functional impairment of the affected joint. It is important to keep this diagnosis in mind when any expansive mass surrounding a joint is observed.